The de-dramatization of history and the prose of bourgeois life - Fulsås, Narve (Nordlit, 2015)
Emperor and Galilean has received renewed interest the last decade. It has been revalued and upgraded, it has been attributed a major role in the development of Ibsen’s authorship, and it has been interpreted as an expression of the new uncertainties of modernity. The play definitely deviates from Ibsen’s earlier historical dramas; it does not hold up an exemplary past or try to emulate a classical style. Rather, it seems to question history as a rational discourse and man’s capacity to create history in a self-conscious way. It is argued that Emperor and Galilean reflects Ibsen’s own experiences, more precisely: his experiences of defeat, estrangement and reorientation connected to the Danish defeat to Prussia-Austria in 1864 and the unification of Germany in the years that followed. Ibsen’s historical experiences were primarily the experiences of counter-finality and historical irony. During the Franco-German war in 1870 he still hoped for a French victory, but a few years later he came to appreciate German unification as a world historical event. The resulting attitude was a kind of fatalism reminiscent of the one we find in Tolstoy’s War and Peace, published a few years earlier, but of course unknown to Ibsen. This fatalism fit well with Ibsen’s conservatism at the time. It left him in a rather ambiguous position, though, and there is no straight literary path leading from Emperor and Galilean to the contemporary plays of the 1880s and 1890s.
Keywords: Emperor and Galilean; history; politics; historical drama; modern drama; Georg Brandes